The Correlation between Food Service Satisfaction, Prison Environment, and Macronutrients Intake with The Nutritional Status of Prisoners in Overcapacity Prison - Syahputra, Bagas Dwi; Santanu, Ayu Mutiara; Insani, Hurry Mega; Astuti, Widya (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
This study aimed to analyze the association of food service satisfaction, prison environment, and macronutrient intake with the nutritional status of inmates. This research employed a quantitative method with a cross-sectional study design. A total of 81 inmates were selected through purposive sampling at class IIB prison in Sumedang Regency. Data collection involved questionnaires, measurements of height and weight, and two 24-hour dietary recall interviews. The results showed that more than half (53.1%) of the subjects were dissatisfied with the food service in the prison. Additionally, (50.6%) of the subjects reported feeling uncomfortable with the prison environment. More than half of the subjects also experienced a deficiency in nutrient intake, including energy (63%), protein (86.4%), and carbohydrates (85.2%). Meanwhile, (72.8%) of the subjects had an adequate fat intake. Based on the chi-square test, a significant relationship was found between the prison environment (p-value=0.000) and energy intake (p-value=0.028) with the nutritional status of the subjects. However, no significant relationship was found between satisfaction with food service (p-value=0.445), protein intake (p-value=0.381), fat intake (p-value=0.053), and carbohydrate intake (p-value=0.192) with nutritional status. Thus, the prison environment and energy intake are associated with inmates’ nutritional status, while food service satisfaction, protein, fat, and carbohydrate intake show no significant relationship.